2011
DOI: 10.4238/2011.november.4.6
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymorphism of the myogenin gene is associated with body measurement traits in native Chinese breeds

Abstract: ABSTRACT. Using PCR-SSCP and DNA sequencing technology, we examined the association of single nucleotide polymorphisms (SNPs) in the bovine MyoG gene with body measurement traits in 779 individuals of six native Chinese cattle breeds, namely Luxi, Luxi × Simmental crossbred, Nanyang, Xia'nan, Jiaxian red, and Qinchuan. A novel SNP, T314C, was detected. Allelic frequencies of MyoG-T/C in the six breeds were 0.8308/0. 1692, 0.8774/0.1226, 0.8021/0.1979, 0.8209/0.1791, 0.8630/0.1370, 0.8044/0.1956, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Through marker-assisted selection studies, many important genes have been identified that have roles in controlling growth (Xue et al, 2011;Tian et al, 2011) and meat quality in livestock (Jiao et al, 2010;Fan et al, 2011). Koo et al (2005) identified CRTC2 as a key regulator for the transcriptional activation of gluconeogenic enzyme, via phosphorylation-dependent cellular localization by AMP-activated protein kinase (AMPK) family of Ser/Thr kinases (Koo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Through marker-assisted selection studies, many important genes have been identified that have roles in controlling growth (Xue et al, 2011;Tian et al, 2011) and meat quality in livestock (Jiao et al, 2010;Fan et al, 2011). Koo et al (2005) identified CRTC2 as a key regulator for the transcriptional activation of gluconeogenic enzyme, via phosphorylation-dependent cellular localization by AMP-activated protein kinase (AMPK) family of Ser/Thr kinases (Koo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Through marker-assisted selection studies, many important genes have been identified to be involved in controlling growth (Xue et al, 2011;Tian et al, 2011) and meat quality in livestock (Jiao et al, 2010;Fan et al, 2011). Studies in mammalian cells have suggested that SIRT2 may play a role in cell cycle regulation and cytoskeleton organization by targeting the cytoskeletal protein tubulin (North et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Growing observations indicate that genetic polymorphisms in myogenin gene are associated with growth traits in livestock. Xue et al [13] identified a novel polymorphism (T314C) in the myogenin gene that was associated with growth traits in native Chinese breeds. Anton et al [14] showed that one SNP in myogenin gene had a strong effect on growth rate in Hungarian large pig.…”
Section: Discussionmentioning
confidence: 99%